THE INFLUENCE OF EDUCATION AND WORK EXPERIENCE ON EMPLOYEE PERFORMANCE THROUGH WORK MOTIVATION - Muriani, Dewi; Kornelius, Yoberth; Kadang, Juliana (Master of Management Study Program, Faculty of Economics and Business, Tadulako University, 2024)
This study is to determine and analyze the mainstreaming of Education, Work Experience, and Work Motivation as mediating variables on employee performance at the Office of the Regional Planning, Research and Development Agency of Sigi Regency. The type of research used is quantitative research. The population in this study were all employees at the Office of the Regional Planning, Research and Development Agency of Sigi Regency. The analytical tool used in this research is Partial Least Squares (PLS) 3.0 with a sample size of 70 respondents. Data collection using questionnaires via Google Forms. The results showed that (1) Education has a positive but insignificant effect on employee performance. (2) Work experience has a positive and significant effect on employee performance. (3) Education has a positive and significant effect on employee work motivation. (4) Work experience has a positive and significant effect on employee work motivation. (5) Work motivation has a positive and significant effect on employee performance. (6) Education indirectly has a positive and significant effect on employee performance through work motivation. (7) Experience indirectly has a positive and significant effect on employee performance through work motivation in employees of the Regional Planning, Research and Development Agency of Sigi Regency.